Huntingtin Co-Isolates with Small Extracellular Vesicles from Blood Plasma of TgHD and KI-HD Pig Models of Huntington's Disease and Human Blood Plasma - Ananbeh, Hanadi; Novak, Jaromir; Juhas, Stefan; Juhasova, Jana; Klempir, Jiri; Doleckova, Kristyna; Rysankova, Irena; Turnovcova, Karolina; Hanus, Jaroslav; Hansikova, Hana; Vodicka, Petr; Kupcova Skalnikova, Helena (International journal of molecular sciences, 2022)
(1) Background: Huntington's disease (HD) is rare incurable hereditary neurodegenerative disorder caused by CAG repeat expansion in the gene coding for the protein huntingtin (HTT). Mutated huntingtin (mHTT) undergoes fragmentation and accumulation, affecting cellular functions and leading to neuronal cell death. Porcine models of HD are used in preclinical testing of currently emerging disease modifying therapies. Such therapies are aimed at reducing mHTT expression, postpone the disease onset, slow down the progression, and point out the need of biomarkers to monitor disease development and therapy efficacy. Recently, extracellular vesicles (EVs), particularly exosomes, gained attention as possible carriers of disease biomarkers. We aimed to characterize HTT and mHTT forms/fragments in blood plasma derived EVs in transgenic (TgHD) and knock-in (KI-HD) porcine models, as well as in HD patients' plasma. (2) Methods: Small EVs were isolated by ultracentrifugation and HTT forms were visualized by western blotting. (3) Results: The full length 360 kDa HTT co-isolated with EVs from both the pig model and HD patient plasma. In addition, a ~70 kDa mutant HTT fragment was specific for TgHD pigs. Elevated total huntingtin levels in EVs from plasma of HD groups compared to controls were observed in both pig models and HD patients, however only in TgHD were they significant (p = 0.02). (4) Conclusions: Our study represents a valuable initial step towards the characterization of EV content in the search for HD biomarkers.
Keywords: Animals; Huntingtonova nemoc; fragment; neurodegenerative disease; biologické markery; Biomarkers; lidé; KI-HD; krevní plazma; prasata; extracelulární vezikuly; proteiny nervové tkáně; TgHD; biomarker; Extracellular Vesicles; Nerve Tissue Proteins; Plasma; exosome; Huntington Disease; Swine; huntingtin; pig model; Huntington´s disease; zvířata; extracellular vesicle; Humans